(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Chedik Higashi Syndrome hasautosomal recessive mode of inheritance, Disorder of cells that contain lysosomal granules and is characterized by partial albinism that affects eyes and skin, severe immune deficiency with consequent increased susceptibility to pyogenic infections. The diagnosis of CHS can only be made on identification of abnormally large granules in the granule-containing cells and leucocytes. Objective: The present study was undertaken so as to increase awareness of CHS thereby ensuring early diagnosis and prompt treatment. Patients and Methods: The study was conducted in Hematology and transfusion Medicine Department. Retrospective review of records of Children diagnosed with CHS between jan 2014 to feb 2016 was undertaken. Results: Total six patients were diagnosed with Chedik Disease in 2years.All patients were male,Average age at diagnosis was 2 years, ages ranged between 3 months to 3 years .All were admitted with complaint of repeated infections and fever and partial albinism. Consanguinity was present in five (83%). Bleeding history was present in two out of six(33.3%) patients and one patient had another affected sibling .On examination 5 out of 6(83%) had hepatomegally, all six (100%)had splenomegaly. All patients were anemic, 4 out of 6 (66.6%) had thrombocytopenia while leucopenia was present in 3 out of six(50%),Pancytopenia being present in 2 out of six(33%)cases. Giant granules were present in myeloid cells in all cases while they were seen in lymphocytes in one case only.Four (66.6%) expired ,one patient is alive while one is lost to follow up. Conclusion: CHS is an uncommon and fatal disorder with variable clinical features and laboratory findings.Delayed referral of these patients to a specialized centres results in under control of infections. Early diagnosis is extremely important and family data and the phenotype suggests the diagnosis.Bone marrow transplant(BMT) is the only curative treatment if performed early,It has little benefit during accelerated phase of CHS,even nonhaploidentical donor BMT, represents an alternative therapy which can, result in change in prognosis.